The Impact of Traffic-Induced Bridge Vibration on Rapid Repairing High-Performance Concrete for Bridge Deck Pavement Repairs - Wei Wang; Shuo Liu; Qizhi Wang; Wei Yuan; Mingzhang Chen; Xiaotian Hao; Shuai Ma; Xuanyu Liang (Advances in Materials Science and Engineering)
Based on forced vibration tests for high-performance concrete (HPC), the influence of bridge vibration induced by traveling vehicle on compressive strength and durability of HPC has been studied. It is concluded that 1 d and 2 d compressive strength of HPC decreased significantly, and the maximum reduction rate is 9.1%, while 28 d compressive strength of HPC had a slight lower with a 3% maximal drop under the action of two simple harmonic vibrations with 2 Hz, 3 mm amplitude, and 4 Hz, 3 mm amplitude. Moreover, the vibration had a slight effect on the compressive strength of HPC when the simple harmonic vibration had 4 Hz and 1 mm amplitude; it is indicated that the amplitude exerts a more prominent influence on the earlier compressive strength with the comparison of the frequency. In addition, the impact of simple harmonic vibration on durability of HPC can be ignored; this shows the self-healing function of concrete resulting from later hydration reaction. Thus, the research achievements mentioned above can contribute to learning the laws by which bridge vibration affects the properties of concrete and provide technical support for the design and construction of the bridge deck pavement maintenance.